(untitled) (New York, 2007)
Step Forward is a standards-based, four-skills course that integrates language instruction into meaningful, real-life contexts. The program ensures learners' mastery of the language related to civics, the workplace, the community, and academics.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Problems, exercises,etc,Giáo trình dành cho sinh viên,Bài tập, bài giải,vv...